2000
DOI: 10.1159/000010237
|View full text |Cite
|
Sign up to set email alerts
|

Transport and Metabolism of Serotonin in the Human Placenta from Normal and Severely Pre-Eclamptic Pregnancies

Abstract: We have attempted to elucidate the possible participation of serotonin as an etiological factor in pre-eclampsia. The transport of serotonin into vesicles from the maternal-facing brush border membrane was measured, as well as the metabolism induced by monoamine oxidase (MAO) in placental homogenate obtained from normal-term and severely pre-eclamptic placentas. Kinetic analysis of serotonin uptake by the placental brush border membrane of the syncytiotrophoblast between normally pregnant and severely pre-ecla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…However, no differences between genotypes at earlier time points (at birth and at pnd10), or even downregulation in Bdnf expression levels in TPH2 −/− in comparison to TPH2 +/+ pnd10 male rats were observed, suggesting that peripheral sources may compensate for the lack of central 5-HT synthesis during the early postnatal periods of life. Indeed, the blood brain barrier is not fully functional before pnd12 (Ribatti et al, 2006 ) and 5-HT from the placenta at embryonic stages (Cool et al, 1990 ; Carrasco et al, 2000 ) and from the peripheral blood after birth may easily enter the brain. Accordingly, Vitalis et al ( 2007 ) demonstrated that the embryonic transient 5-HT depletion did not modify cortical BDNF levels until PND21 in pups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no differences between genotypes at earlier time points (at birth and at pnd10), or even downregulation in Bdnf expression levels in TPH2 −/− in comparison to TPH2 +/+ pnd10 male rats were observed, suggesting that peripheral sources may compensate for the lack of central 5-HT synthesis during the early postnatal periods of life. Indeed, the blood brain barrier is not fully functional before pnd12 (Ribatti et al, 2006 ) and 5-HT from the placenta at embryonic stages (Cool et al, 1990 ; Carrasco et al, 2000 ) and from the peripheral blood after birth may easily enter the brain. Accordingly, Vitalis et al ( 2007 ) demonstrated that the embryonic transient 5-HT depletion did not modify cortical BDNF levels until PND21 in pups.…”
Section: Discussionmentioning
confidence: 99%
“…Since in adulthood it cannot pass the blood-brain barrier, these two enzymes define two 5-HT systems with independent regulation and different function. Although in the adult brain 5-HT is produced only by serotonergic neurons in raphe nuclei, during development there are other sources of this monoamine, including maternal 5-HT, that is actively transported through the placental brush border cells via the serotonin transporter (SERT; Cool et al, 1990 ; Carrasco et al, 2000 ; Kliman et al, 2018 ). Moreover, until postnatal day (pnd) 12, the blood-brain barrier is immature (Ribatti et al, 2006 ) and 5-HT, produced by TPH1 starting at embryonic day 14 in rodents (Côté et al, 2007 ) can reach the brain.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, there are multiple sources of 5-HT in the developing brain. The first and most important source is the mother: maternal 5-HT is actively transported through the placental brush border cells via SERT (Cool et al, 1990;Carrasco et al, 2000). 5-HT immunostaining is present in the placenta and the ectoplacental cone (Yavarone et al, 1993).…”
Section: -Ht Sources During Developmentmentioning
confidence: 99%
“…1). Once inside the syncytiotrophoblast, serotonin is metabolized by monoamine oxidase, an enzyme present abundantly in the placenta (Carrasco et al, 2000; Sivasubramaniam et al, 2002). Thus, the syncytiotrophoblast functions like a sink for serotonin.…”
Section: Effects Of Cocaine and Amphetamines On Pregnant Women – Presmentioning
confidence: 99%